Back Matter Vol 17 No 2, 2025 - Indonesian Journal of Social Sciences (Indonesian Journal of Social Sciences, 2025)
The back matter contains guidelines for authors, an index of authors, an index of subjects, and the back cover of volume 17, issue 2 (2025).